Os jogos de linguagem entre surdos e ouvintes na produção de significados de conceitos matemáticos - Moreira, Ivanete Maria Barroso (2015)
This work shows the result of a research that has the purpose to analyze the language games between the deaf and listener subjects and their collaboration to comprehension and ressignification of mathematic concepts in an inclusive classroom. This comprehension is associated to the translation of mathematic texts to the Portuguese language, and from this to the sign language, in a discursive round trip. This happens in the subjects’ way of life in the classroom like: the deaf student’s lip reading, the teacher’s explanation, the professional interpreter’s function of interpreting when it’s intermediating the dialogues – from the deaf student to the teacher, from the teacher to the deaf student, from the deaf students to the listener students and vice versa. This translation confirms itself in the modalities: oral, written and signed, confirming the theses of “The relation between sign, Portuguese and mathematic languages in an inclusive classroom environment produce language games between the deaf and listener subjects in attempt to understand the mathematic concepts.” The research is guided by the studies of the philosopher Ludwig Wittgenstein, on his second phase – postmortem – and his conceptions about: the language games and the use of rules. The research’s locus was an inclusive classroom of the 3rd year of the High School of an Ananideua’s Municipal School and as subjects were selected five deaf students, seven listener students, a LIBRAS interpreter and a math teacher. The collection of empirical material for the research was by the means of: observation; recording (video and audio); questionnaires; interviews; logbooks’ notes; and activities in the math’s classes. The data’s analyzes are disposed in two levels: i) the language games between the deaf and listener subjects in an inclusive classroom (teacher, interpreter, dead students and listener students) and ii) use of language rules in the teaching of mathematical content (Equation of Circle and Complex Numbers). The samples of analyzes revealed results such as: the existence of ‘particular rules’ previously established between the discursive relations of the deaf and the listener subjects; the care of the interpreters must have in the literal interpretation of the words with various meanings, the polysemy of the Portuguese and the sign languages; the difficulty in translate the mathematic language into the sign language, because the lack of specific mathematical signs in LIBRAS and the endless contract between interpreters and deaf students with different differential signals, which difficult to organize the teaching and the translation; and also we had the confirmation that the incursive classroom, as much in any environment, context, where there’s relations, humans interactions, exist a variety and a plurality of language games.